Hand-wrist and cervical vertebral maturation indicators: how can these events be used to time Class II treatments? - Grave Keith; Townsend Grant (Sciendo, 2003)
Background: Ossification events in the hand and wrist and in the cervical vertebrae have been shown to occur at specific times before, during and after the adolescent growth spurt, but there is still debate about the applicability of these findings to the clinical management of Class II cases. The aim of this study was to relate, on an individual basis, cervical vertebral maturation stages and hand-wrist ossification events to the timing of peak statural and mandibular growth in a group of indigenous Australians.